Pengaruh Penggunaan Media Pembelajaran Genially Terhadap Kemampuan Menulis Teks Berita Pada Siswa Kelas XI SMK Marisi Medan - Sitanggang, Nelva Elvryani; Sitohang, Tigor; Wulan, Eka Putri Saptari (Lembaga Riset dan Inovasi Almatani, 2025)
This study aims to determine the significant effect of using Genially learning media on the news text writing skills of Grade XI students at SMK Marisi Medan. The research employed a quasi-experimental method with a posttest-only control group design. The population of the study consisted of 135 students, with a sample of 70 students divided into two groups: class XI TKJ (35 students) as the experimental group, which received treatment using Genially media, and class XI TBSM (35 students) as the control group, which was taught using conventional learning methods. The research instrument was a subjective writing test on news texts, assessed based on a rubric covering the aspects of news elements, text structure, linguistic features, and thematic relevance. The findings of the study showed that the use of Genially learning media had a significant effect on improving students' news text writing skills. The average score before using Genially was 43.5 (categorized as poor) with a standard deviation of 15.48. The highest score was 65, and the lowest was 15. The average posttest score after using Genially was 50.59 (categorized as good), with a standard deviation of 21.63. The highest posttest score was 85, and the lowest was 10. Based on data analysis using the t-test, the result showed tcount = 2.83, which is greater than the ttable value = 1.68 at a significance level of 0.05, indicating that tcount > ttable (2.83 > 1.68). These findings support the alternative hypothesis (Ha) that the use of Genially media is effective in enhancing students’ news text writing skills. This is especially due to its interactive, visual, and multimedia features, which help students understand the structure, language elements, and context of news writing more easily. This study recommends the use of Genially as an innovative learning medium to improve writing skills and increase student engagement in Indonesian language learning.